Noise levels measuring during summer and winter in pigs’ farm - Sistkova, Marie; Bartos, Petr; Broucek, Jan; Dolan, Antonin; Celjak, Ivo (Scientific Journal of Environmental Sciences, 2014)
The objective of this study was to find potential impacts on the creation and propagation of sound from pig’s barn. The hypothesis that the sound generated from pig housing would be influenced by the season and distance from the noise source was tested. The research was carried out in the barn for fattening pigs during summer and winter. The measurements were made indoors and outdoors the barn. At summer were recorded significantly higher noise levels outdoors (43.79±1.18 dB vs. 42.30±1.75 dB, P<0.001) than during winter. Significant difference between summer and winter was also calculated indoors of barn (65.03±1.60 dB vs. 63.84±1.44 dB, P<0.01). The measured values were in all cases higher indoors the building than outdoors. However, averages did not significantly differ in comparison of 7 m and 11 m distances from sidewalls. The results indicated that noise emitted from the pigs housing is dependent on the season of year and distance from building.